ANALISA KUALITAS PELAYANAN, KELENGKAPAN FASILITAS, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KEPUASAN KONSUMEN DI LABORATORIUM KLINIK PARAHITA YOGYAKARTA - eka apriyanto (JURNAL EKOBIS DEWANTARA, 2018)
ABSTRACT This research has a purpose: (1) To analyze the influence of service quality variable to customer satisfaction at Parahita Clinical Laboratory Yogyakarta. (2) To analyze the influence of facilities completeness variable to customer satisfaction at Parahita Clinical Laboratory Yogyakarta. (3) To analyze the influence of competence of human resources variable to consumer satisfaction at Parahita Clinical Laboratory Yogyakarta. (4) To analyze the influence of service quality variable, facilities completeness variable, and competence of human resources variable to customer satisfaction at Parahita Clinical Laboratory Yogyakarta. Variables in this research are the service quality, facilities completeness, competence of human resources, and customer satisfaction. Methods of data collection using questionnaires. The analysis technique used is multiple linear regression with 5% significance level. The results of hypothesis testing: (1) Service quality not influence on customer satisfaction at Parahita Clinical Laboratory Yogyakarta. (2) Facilities completeness influence on customer satisfaction at Parahita Clinical Laboratory Yogyakarta. (3) Competence of human resources influence on consumer satisfaction at Parahita Clinical Laboratory Yogyakarta. (4) Service quality, facilities completeness, and competence of human resources influence on customer satisfaction at Parahita Clinical Laboratory Yogyakarta.